Consumers' awareness and consumption intention towards green foods - Rezai, Golnaz; Phuah, Kit Teng; Mohamed, Zainal Abidin; Shamsudin, Mad Nasir (Academic Journals, 2012)
Consumers’ food consumption patterns are changing rapidly. Consumers become more concern about the food they consume. They tend to consume foods that are nutritious, healthy, safe and friendly to the environment and animals. Thus the green concept is now steadily being disseminated among consumers in conjunction with sustainable and conservation of agricultural development. Green foods refer to foods that are safe to be consumed, fine quality and nutritious food produced under the principle of sustainable development. This paper focuses on the consumers’ awareness and intention towards green foods consumption in Malaysia. The Theory of Plan Behavior (TPB) is applied in this study. Structured questionnaire was design as an instrument to gather information on green food consumer behavior. A survey was conducted in late 2010 and 1355 respondent’s response to the questionnaire. Descriptive statistic and chi-square analyses were used to analyze the data collected. The results indicate that most respondents are aware about the green concept. The results also shows that there are significant different among the respondents awareness towards green food and age, geographical area, education level and income. Respondent’s also indicates that green food is not only about organic but it encompasses the concept of food safety, health issues, environmental hazard as well as animal welfare. Thus most respondents are aware of the green concept and this is a strong indicator of consumers’ intention to go green in food consumption.